Mode competition mechanism of D-band coaxial static magnetic wiggler - Liang Zhang; Yan Teng; Yongdong Li; Hongguang Wang; Yue Wang; Feng Zhang; Wenjin Yang; Yonggui Zhai (AIP Advances)
The coaxial static magnetic wiggler is a compact and efficient narrowband generator that utilizes the interaction between an annular electron beam and coaxial TE01 mode to generate electromagnetic radiation through a self-feedback mechanism. It has the potential to produce terahertz radiation with power levels up to hundreds of megawatts. However, previous research has primarily focused on frequencies below 0.1 THz, with limited studies on the D-band and higher frequency bands. Many mechanisms and principles remain insufficiently explored, making it difficult to enhance output power and conversion efficiency at higher frequencies. To address these issues, we investigated the mode competition mechanisms in a D-band coaxial magnetostatic wave undulator and explored methods to suppress mode competition through theoretical analysis and three-dimensional full electromagnetic particle-in-cell simulations. Employing these methods to enhance the mode competition capability of the TE01 mode and suppressing that of higher-order TE modes, the wave-beam conversion efficiency can be significantly improved. After suppressing mode competition, the coaxial static magnetic undulator designed in this study achieved an output power of 140 MW at 152.99 GHz with a conversion efficiency of 15.7%.